(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
A refined subdivision, based on fusulinids, of the Moscovian stage in southwestern Darvaz is proposed. Seven local zones, three in the Lower Moscovian substage and four in the Upper Moscovian substage were established, based on investigations of three stratigraphic sections. The zones were correlated with those of the Eastern European and Middle Asian stratigraphic schemes. One hundred and forty-three species and subspecies, which belong to 29 genera and 13 families of fusulinids, were identified in the Middle Carboniferous of Darvaz. Among them, one genus (Undatafusulina) and 16 species, i.e. Taitzehoella compacta, Ovatella panjensis, Aljutovella darvasica, Undatafusulina asiatica, Citronites panjensis, C. reticulatus, Beedeina darvasica, B. dutkevichi, Putrella admiranda, Hemifusulina orientalis, Fusulinella (Moellerites) subundulata, F. (M.) jucunda, F. (M.) orientalis, F.(Fusulinella) crassitectoria, F. (F.) bogushi, and F. (F.) pamirensis are new.